Interaction between polyacrylate coatings used in controlled-release fertilizers and soils in wheat-rice rotation fields - Liang, Dong; Du, Changwen; Ma, Fei; Shen, Yazhen; Wu, Ke; Zhou, Jianmin (Agriculture, ecosystems & environment, 2019)
•The interactions between polyacrylate and farmland soil were investigated.•polyacrylate coatings were characterized by FTIR-PAS and LIBS.•The behavior of polyacrylate coatings in the farmland soil was explored.•The environmental impacts of polyacrylate coating were evaluated. In recent years, Polyacrylate (PA) coatings have been used in controlled-release fertilizers (CRFs), and the impact of PA coatings on the soil environment is becoming a concern. However, the interaction between PA coating and soil remains unclear. In this study, the interaction between PA coatings and soils in the field of wheat and rice was investigated. The coatings were buried in the outdoor wheat land and rice field for 12 months. The residual coatings and the nearby soils were analyzed by Scanning electron microscopy (SEM), (Fourier transform mid-infrared photoacoustic spectroscopy (FTIR-PAS), laser induced breakdown spectroscopy (LIBS), and Biolog Ecoplates. After 12 months, the erosion of PA buried in the wheat land was faster than that buried in the rice field, and the weight loss was 1.69% and 1.46%, respectively. FTIR-PAS showed that the intensity of C H and C − O bonds in PA buried in the wheat field became weaker than that buried in the rice field. LIBS showed that PA buried in the wheat land adsorbed more soil elements, such as N, P, K, Ca, Si, than that buried in the rice field. There were no significant impacts of the PA coatings on the spectral properties or microbial community function of soils. The high temperature, high humidity and high microbial activity in the soils could accelerate the coating erosion. The results demonstrated that the PA coatings were biodegradable and environmentally friendly in the fields of wheat and rice when applied in CRFs.